(untitled) (Research, Society and Development, 2021)
Objective: To identify the sociodemographic and clinical characteristics of users with Chronic Noncommunicable Diseases (NCDs) treated at a hospital emergency service. Methodology: This is a quantitative cross-sectional survey, carried out on the electronic medical record of 364 patients diagnosed in at least one of the four main groups of NCDs, according to the International Classification of Diseases (ICD), in an emergency service of a hospital highly complex public located in the northwest of the State of São Paulo. Descriptive statistics were used for data analysis. Results: There was a predominance of male patients (53.3%), married (56.0%), with incomplete elementary education (49.2%) with an average age of 62.7 years. The most prevalent diagnosis (77.7%) was cardiovascular diseases (CVDs). The comorbidities most frequently associated among study participants were Systemic Arterial Hypertension (SAH) (31.9%), followed by smoking (22.3%), dyslipidemia (19.2%) and alcoholism (16.5%). Of the study participants, 80.4% had complications related to their main diagnosis, the main complication being previous stroke (18.4%). The most used medication for treatment among the participants was the class of antihypertensive drugs. In addition, extensive errors were found in the records of users’ medical records, resulting in underreporting. Conclusion: Knowing the profile of users who attend hospital emergency services becomes essential considering that it is often the aggravation of NCDs, which could be minimized if there was a more effective monitoring of the user in Primary Healthcare, reducing unplanned hospitalizations, as well as spending and overcrowding of emergency services.